Micellar drug delivery - Cellesi, Francesco (Henry Stewart Talks, 2020)
The definition of micelles, Micelles formation, Critical micelles concentration, Micelles characteristic: size shape and drug encapsulation, Methods of drug encapsulation, Micelles as nanocarriers, Micelle design for drug delivery, Advanced drug delivery strategies: multifunctional micelles, stimuli responsive micelles, pH sensitive micellular pro-drug system, cisplatin loaded micelles